Technical and Non-Technical Factors of Risk Identification for Sustainable Coastal Development in Malaysia - Azimi, Mohd Azrulfitri; Zakaria, Sharifah Akmam Syed; Majid, Taksiah A. (IPTEK Journal of Proceedings Series, 2017)
Â¾ In recent years, human casualties and economic losses caused by natural disasters in Malaysia have been increasing, with infrastructure development is becoming concentrated in disaster-prone areas. Urbanized coastal cities are also growing in number and size with high-rise buildings widely built along the shorelines. Every community is at risk from natural hazards, which creates an urgent need for public policies and strategic plans to manage the inevitable risks. Thus, this study aims to explore the technical and non-technical factors of disaster risks pertaining infrastructure development for sustainability along the coastal areas of Malaysia. It is also intended to find the common aspects of these technical and non-technical factors that can be built as an integral part of disaster risk management. Specifically, this study presents evidence using a quantitative analysis for classifying and ranking technical and non-technical factors of disaster risks from an open-ended feedback on a given hypothetical case study pertaining infrastructure development along coastal areas. The results reflect that the technical factors of disaster risks include engineering measures and construction of hazard-resistant and protective infrastructures, while the non-technical-factors include policies, awareness and the provision of information. Determining the risk factors that enable communities and policy makers make well-informed decisions for long-term sustainable development represents national and local priorities with a strong institutional basis for implementation.